Cutaneous allodynia as predictor for treatment response in chronic migraine: a cohort study - Pijpers, Judith A.; Kies, Dennis A.; van Zwet, Erik W.; de Boer, Irene; Terwindt, Gisela M. (Journal of headache and pain, 2023)
Background Central sensitisation is an important mechanism in migraine chronification. It is presumed to occur in second and third order neurons sequentially, resulting in an analogous spatial distribution of cutaneous allodynia with cephalic and extracephalic symptoms. We investigated whether allodynia, and its subtypes based on spatial distribution and type of stimulus, predict response to treatment in chronic migraine patients. Methods This study was conducted as part of the CHARM study (NTR3440), a randomized, double-blind, placebo-controlled trial in chronic migraine patients with medication overuse. We included 173 patients. The presence of cutaneous allodynia at baseline was established with the Allodynia Symptom Checklist. Primary endpoint was reversion from chronic to episodic migraine. Results Of all patients, 74.6% reported cutaneous allodynia. Absence of allodynia compared to presence of allodynia was predictive for reversion from chronic to episodic migraine, odds ratio (OR): 2.45 (95% CI: 1.03–5.84), p = 0.042. The predictive value was more pronounced when subdivided for spatial distribution, for participants without allodynia versus cephalic (OR: 4.16 (95% CI: 1.21–14.30), p = 0.024) and extracephalic (OR: 7.32 (95% CI: 1.98- 27.11), p = 0.003) allodynia. Mechanical, but not thermal, allodynia, was associated with outcome. Conclusions Cutaneous allodynia, an important marker for central sensitization, likely has predictive value for treatment response in chronic migraine. Graphical Abstract